An Improved Space Vector Modulation for Short-Circuit Fault-Tolerance in Multi-Level Hybrid-ANPC - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (ICEMS 2021 - 2021 24th International Conference on Electrical Machines and Systems, 2021)
Power converters are opposed to the danger of short circuit faults and regarded as a serious issue in terms of stable and reliable operation. This paper introduces a creative method for tolerating the short circuit faults by generating a new switching sequence and reference signals in hybrid active natural point clamped converters (ANPC). In these regards, the operation under short circuit faults is analyzed. Correspondingly, the proposed fault tolerance strategy is explained and clarified. The proposed strategy maintains a healthy operation under the faulty conditions without a need for including any additional hardware. In addition, it can be applied to the hybrid ANPC converters without any special requirements to withstand under high voltage levels.
Keywords: Creatives; Faulty condition; Hybrid active natural point clamped converter; Multilevels; Reference signals; Reliable operation; Short-circuit fault; Space Vector Modulation; Stable operation; Switching sequence; Fault-tolerance; hybrid ANPC; short circuit